The Role of Al-Jurjani and Farid Wajdi in the Development of Arabic Language and Literature Studies - Muhammad Bilal; Reziq Ridho (Pascasarjana Universitas Islam Negeri Mataram, 2024)
In this study, we focus on Keer course of Abdul Qahir al-Jurjani in the themes of Farid Wajdi and consider the importance of these thoughts in recent studies on the Arabic language and literature. While Al-Jurjani established a rhetorical theory, focusing on links between structure and meaning of individual sentences, Farid Wajdi presented a linguistic method, ground on social and cultural approaches. This study employs a library research approach in a qualitative research model. The findings show Al-Jurjani made significant contributions to understanding the aesthetics of language through his theories on structure and meaning, which form the foundation of balaghah. At the same time, Farid Wajdi advocated a broader view of Arabic linguistics that brought together language and society in a new paradigmatic dialectology and sociolinguistics. The theoretization provided by the work of these two heralds exceedingly augmented the field of the Arabic language and literature along with forming methodological basis for the fields of Qur'anic exegesis, literary criticism.